2019
DOI: 10.1101/750869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct cellular mediators drive the Janus Faces of Toll-like Receptor 4 regulation of network excitability which impacts working memory performance after brain Injury

Abstract: AbstractThe mechanisms by which the neurophysiological and inflammatory responses to brain injury contribute to memory impairments are not fully understood. Recently, we reported that the innate immune receptor, toll-like receptor 4 (TLR4) enhances AMPA receptor (AMPAR) currents and excitability in the dentate gyrus after fluid percussion brain injury (FPI) while limiting excitability in controls. Here we examine the cellular mediators underlying TLR4 regulation of dentate exci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In addition, excitability of the cerebral dentate gyrus after brain injury accompanied by increased TLR4 signaling is mediated by the synaptic AMPAR current, while the NMDAR, another glutamate receptor, does not change [18]. Consistent with this, blocking of TLR4 signaling after brain injury can reduce the calcium-permeable AMPAR current of granular cells in the dentate gyrus, reduce neural network excitability and epilepsy susceptibility [19,20]. Based on the above studies, we speculate that AR-induced OD may be accompanied with AMPAR-mediated neuronal damage induced by microglia activation, and dopamine D2 receptor agonists are expected to reverse this process.…”
Section: Introductionmentioning
confidence: 70%
“…In addition, excitability of the cerebral dentate gyrus after brain injury accompanied by increased TLR4 signaling is mediated by the synaptic AMPAR current, while the NMDAR, another glutamate receptor, does not change [18]. Consistent with this, blocking of TLR4 signaling after brain injury can reduce the calcium-permeable AMPAR current of granular cells in the dentate gyrus, reduce neural network excitability and epilepsy susceptibility [19,20]. Based on the above studies, we speculate that AR-induced OD may be accompanied with AMPAR-mediated neuronal damage induced by microglia activation, and dopamine D2 receptor agonists are expected to reverse this process.…”
Section: Introductionmentioning
confidence: 70%
“…In the rat DG, neuronal TLR4 increased after fluid percussion injury, while electrophysiological records showed that TLR4 activation enhanced dentate network excitability in injured rats (Korgaonkar et al, 2020a; Li et al, 2015). As AMPA currents in neuronal cultures depleted of glia were enhanced by agonists of TLR4 and reduced by TLR4 antagonists, it was believed that neuronal TLR4 signaling enhances excitability in the injured brain (Korgaonkar et al, 2020b). These experiments suggest that neuronal TLR4 modulates dentate excitability.…”
Section: Discussionmentioning
confidence: 99%
“…As the authors mention, it could be due to differential recruitment of glial versus neuronal signaling. Globally, neuronal TLR4 signaling is predominant in pathological situation, at least in adult rats, underlying an increased excitability in the DG (Korgaonkar et al, 2020b). However, these studies concerned early posttraumatic injury events and reveal modulation of neuronal excitability by TLR4 signaling in the DG only, while our present observation concerned the CA1 area.…”
Section: Discussionmentioning
confidence: 99%